2013
DOI: 10.1017/s1463423613000133
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility trial of GP and case-managed support for workplace sickness absence

Abstract: The design was a feasibility-controlled trial in which participants were sickness absentees, or presentees in employment with work-related health problems. Individuals completed health status measures (SF-36; EQ-5D) and a Job Content Questionnaire at baseline and again at four-month follow-up. Findings In the intervention group, 29/60 participants completed both phases of the trial. GP practices referred two control patients, and, despite various attempts by the research team, GPs failed to engage with the tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Of those studies that have tested interventions to manage work absence in those with health conditions [ 47 , 48 ], the Fit for Work Service pilots tested different models of delivering vocational advice however only 21% of referrals came from general practice [ 48 ]. A more recent UK study aiming to provide vocational advice in primary care lacked GP engagement leading to poor recruitment [ 49 ]. The SWAP trial was therefore the first to provide an early VAI, embedded in UK general practice, to people with musculoskeletal pain, a leading cause of work absence.…”
Section: Discussionmentioning
confidence: 99%
“…Of those studies that have tested interventions to manage work absence in those with health conditions [ 47 , 48 ], the Fit for Work Service pilots tested different models of delivering vocational advice however only 21% of referrals came from general practice [ 48 ]. A more recent UK study aiming to provide vocational advice in primary care lacked GP engagement leading to poor recruitment [ 49 ]. The SWAP trial was therefore the first to provide an early VAI, embedded in UK general practice, to people with musculoskeletal pain, a leading cause of work absence.…”
Section: Discussionmentioning
confidence: 99%
“…These include clinical knowledge which was not found to be a key requirement in either a systematic review or focus groups with vocational advisors [26,27]. It has been suggested that interpersonal skills may be more important than a health background when defining the VA role [29,30]. The level of clinical knowledge required for the VA role is centred on understanding the potential for disability or functional limitations that a condition leads to, and hence the likely impact on work participation [24].…”
Section: Discussionmentioning
confidence: 99%
“…In intervention practices, VAs actively engaged in practice life, joining breaks and staff meetings and providing both formal and informal feedback about the service to GPs. This was important, given the difficulty in engaging GPs in studies of VA and has been reported by Rannard et al 26 and the Fit for Work pilots. 18 The finding that there was a difference in GP-certified periods of absence could have been related to the visibility of the VAs in the practice, suggesting that raising the profile of available VA services providing VA may be of benefit.…”
Section: Strengths and Limitationsmentioning
confidence: 99%